(untitled) - Uwe Schoning (Boston, Massachusetts, 1989)
This book introduces the notions and methods of formal logic from a computer science stanpoint, covering propositional logi, predicate logic, and foundations of logic programming. It presents such modern applications and themes of current computer science research as resolution, automated deduction, and logic programming in a rigorous but readable way
Keywords: logic programming,logic, symbolic and mathematical